Provisions of return in the gift - Abdedaim, hadjer (Journal of Human Sciences, 2023)
This study aims to shed light on the provisions of the return of the gift, which is considered one of the interesting topics that raise a lot of controversy in the jurisprudential and legal fields together. What he will do in terms of behavior, so he must be aware of the extent to which he can withdraw from this gift, and in order to achieve the essence and purpose of his donation. And the most important thing that highlights the importance of the subject, in addition to the seriousness of the behavior itself, which raises the permissibility of returning the gift? What is the nature of that return and what is its impact?